Smart phone-assisted colorimetric detection of iron using Terminalia chebula coated amine functionalized mesoporous silica nanoparticles - Arighna Saha; Snehasis Bhakta; Goutam Biswas (Next Materials)
Iron (Fe) is an important element for most of the living organisms. Excessive iron consumption can lead to several health issues. Herein, we developed a simple, cost-effective, smartphone-assisted colorimetric detection strategy for both Fe2 + and Fe3+. Extract from Terminalia chebula (T. Chebula) can show a color change from yellow to blue when interacting with iron. By applying this simple chemistry, we synthesized T. Chebula-coated APTES functionalized mesoporous silica nanoparticles (TC-APTES@MSN) and detected iron in water. The white color, porosity of MSN, amine functionalization from APTES, and sensing property of T. Chebula synergistically work to enhance the sensing mechanism. The application of the APTES coating altered the surface charge from negative to positive, effectively facilitating the coating of T. Chebula on the white background of MSN. Subsequent color changes following the interaction with Fe2+ and Fe3+ ions ultimately elucidated the entire sensing mechanism. All the synthesis steps were thoroughly characterized using Raman spectroscopy, infrared spectroscopy, scanning electron microscopy (SEM), and thermogravimetric analysis. We used an iPhone 13 camera to capture images of different colors and analyzed them using ImageJ software to extract the R, G, and B values. Finally, the PLS regression method was applied to establish an equation that can be used to determine the unknown concentration of Fe ions. Although the detection strategy is similar to the spectrophotometric method, it is rapid, easy, and cost-effective . This TC-APTES@MSN sensor could detect very low concentrations of 5 ppm and a maximum of up to 20 ppm for both Fe2+ and Fe3+ in aqueous solution; beyond this concentration, the surface color of the sensor became indistinguishable.